Investigating Some Bacterial Sensitivity upon Ethanolic and Aqueous Extract of Some Medicinal Plants - Kadhim, Oday J. (International Journal of Psychosocial Rehabilitation, 2020)
The current study investigated both crud alcoholic and aqueous extracts of Citrullus colocynthis fruits, Matricaria chamomilla flowers and Mentha longifolia leaves, in order to identify active compound and their biological activities on some pathogenic bacteria. Results show that Citrullus extract contains Alkaloids, Tanins, Terpenoids, Steroids and Saponins. Whilst Matricaria extracts showed positive results to the appearance of Alkaloids, Glycosides, Tanins, Steroids and Phenolic Compounds . Mentha extracts had Alkaloids, Tanins, Steroids and Phenolic Compounds. Biological activities result showed significant effect of all extracts in Staphylococcus aureus, Staphylococcus epedermids, Streptococcus pyogens, Klebseilla pneumonia and Escherichia coli in-vitro. Maximal peak of inhibition zone in Citrullus was (15mm) of E. coli upon ethanolic extract while minimal inhibition zone was (11mm) for aqueous extract of K. pneumonia. Matricaria flower recorded highest inhibition zone of (20mm) of Staph. aureus bacteria for aqueous extract and inhibition zone of (10mm) of E. coli for ethanolic extract. Mentha leaves recorded highest inhibition zone of (18mm) in (E. coli and Staph. aureus) for the ethanolic extract, while the lowest inhibition zone of (12 mm) in Staph. epedermids in the aqueous extract. Over all, alcoholic extract were more effective than aqueous in inhibiting bacterial growth.